Perceptions and barriers: Understanding mental illness stigma among patients in Malaysia - Suhardi, Dayang Nur Syahidah Abang; Razali, Asbah; Razali, Nur Azah; Hashim, Nurhamizah; Mansur, Akhmad (Masyarakat, Kebudayaan dan Politik, 2024)
Previous research on patients, families and communities has discussed the perception of mental illness and how stigma has a very constant impact on every aspect of the lives of individuals with mental illness. However, this issue has not been studied in the Malaysian context until now. The purpose of this study is to explore the perceptions and experiences that mental health patients with stigma have in Malaysia, as well as how it affects their daily lives. This qualitative research was conducted in Kuala Lumpur using semi-structured interviews with eight university students (three males and five females) undergoing outpatient treatment. Informants were selected using the snowball method, and with diagnoses that included depression, anxiety, eating disorders, bipolar disorder, and schizophrenia. Qualitative thematic analysis was used to identify themes regarding patients’ experiences of stigmatization, negative impacts, and solutions to overcome them. The results showed that social stigma is caused by the social environment, particularly through relationships with family and friends, potentially placing patients in a more intrusive environment, which reduces the level of support available during recovery. The study concluded that for those with mental illness, stigma is a pervasive landmine that they face daily through hurtful comments or jokes.